Life-time expression of the proteins peroxiredoxin, beta-synuclein, PARK7/DJ-1, and stathmin in the primary visual and primary somatosensory cortices in rats - Böhm, Michael R. R.; Melkonyan, Harutyun; Thanos, Solon (Frontiers in Neuroanatomy, 2015)
Four distinct proteins are regulated in the aging neuroretina and may may be regulated in the cerebral cortex, too: peroxiredoxin, beta-synuclein, PARK[Parkinson disease(autosomal recessive, early onset)]7/DJ-1, and Stathmin. Thus, we performed a comparative analysis of these proteins in the the primary somatosensory cortex (S1) and primary visual cortex (V1) in rats, in order to detect putative common development-, maturation- and age-related changes. The expressions of peroxiredoxin, beta-synuclein, PARK[Parkinson disease (autosomal recessive, early onset)]7/DJ-1, and Stathmin were compared in the newborn, juvenile, adult, and aged S1 and V1. Western blot, quantitative reverse-transcription polymerase chain reaction, and immunohistochemistry analyses were employed to determine whether the changes identified by proteomics were verifiable at the cellular and molecular levels. All of the proteins were detected in both of the investigated cortical areas. Changes in the expressions of the four proteins were found throughout the life-time of the rats. Peroxiredoxin expression remained unchanged over life-time. Beta-Synuclein expression was massively increased up to the adult stage of life in both the S1 and V1. PARK[Parkinson disease (autosomal recessive, early onset)]7/DJ-1 exhibited a massive up-regulation in both the S1 and V1 at all ages. Stathmin expression was massively down regulated after the neonatal period in both the S1 and V1. The detected protein alterations were analogous to their retinal profiles. This study is the first to provide evidence that peroxiredoxin, beta-synuclein, PARK[Parkinson disease (autosomal recessive, early onset)]7/DJ-1, and Stathmin are associated with postnatal maturation and aging in both the S1 and V1 of rats. These changes may indicate their involvement in key functional pathways and may account for the onset or progression of age-related pathologies.